Abnormalities of factor VIII related protein multimers in the haemolytic uraemic syndrome. Issue 12 (December 1984) - Rose, P E; Enayat, S M; Sunderland, R; Short, P E; Williams, C E; Hill, F G
Abstract : Factor VIII related activities and factor VIII related antigen multimeric analysis have been assessed in two sporadic and eleven epidemic cases of haemolytic uraemic syndrome. In all patients factor VIII related antigen was raised and had an abnormal multimer pattern at presentation. The return to normal of factor VIII related antigen values and multimeric analysis patterns paralleled clinical improvement and, therefore, may be useful in monitoring patients with haemolytic uraemic syndrome. We postulate that endothelial cell damage releases the abnormal high molecular weight factor VIII related antigen multimers and that this may cause platelet agglutination in vivo.